Boletellus brunoflavus sp. nov. (Boletaceae, Basidiomycota) from Baiyun Mountain, Guangzhou, China - Lin, Zhi-Jun; Huang, Xiao-Xia; Liang, Ying-Shan; Qiu, Li-Hong (Phytotaxa, 2022)
Boletellus brunoflavus sp. nov. collected from Baiyun Mountain, Guangzhou, China, is described based on 5-locus (nrITS, nrLSU, rpb1, rpb2 and tef1-α) phylogenetic analyses and morphological examination. It is characterized by small to medium size basidiomata; dry, sparse tomentose and brownish yellow pilei with reddish brown tints; a golden to brownish yellow hymenophore; relatively small basidiospores with longitudinal striae only and pale yellowish context turning greenish blue immediately when bruised.